2003
DOI: 10.1007/s00122-002-1165-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and breeding behavior of pentaploids derived from 3x × 4x crosses in potato

Abstract: Cytology and breeding behavior of Solanum commersonii - S. tuberosum hybrids derived from 3 x x 4 x crosses was examined. The chromosome number of hybrids ranged from hypo-pentaploid (2 n=5 x - 8=52), to hyper-pentaploid (2 n=5 x + 7=67), with the euploid pentaploid 2 n=5 x=60 class predominant. The high variability in chromosome number of the 3 x x 4 x hybrids was attributed to the fact that meiotic restitution during megasporogenesis of the 3 x female may have involved poles with various chromosome numbers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Homoeologous pairing was also observed in PMC from the BC 1 and BC 2 progenies, showing mostly multivalents (16 on average in the BC 1 and 13 in the BC 2 ) with relatively few bivalents and very few univalents. It appears to be higher than that observed by Barone et al (1999) and Carputo (2003). Put together, our chromosome pairing evidence indicates that the F 1 triploid hybrids between S. commersonii and S. tuberosum Group Phureja behave as autotriploids and that homoeologous recombination can take place among all their chromosomes.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Homoeologous pairing was also observed in PMC from the BC 1 and BC 2 progenies, showing mostly multivalents (16 on average in the BC 1 and 13 in the BC 2 ) with relatively few bivalents and very few univalents. It appears to be higher than that observed by Barone et al (1999) and Carputo (2003). Put together, our chromosome pairing evidence indicates that the F 1 triploid hybrids between S. commersonii and S. tuberosum Group Phureja behave as autotriploids and that homoeologous recombination can take place among all their chromosomes.…”
Section: Discussionmentioning
confidence: 42%
“…In our case BC 1 plants were aneuploid, while Barone et al (1999) found that most were exact allopentaploids. The cases of 5x-aneuploids were explained in terms of occasional omission of chromosomes in the restitution nuclei forming 2n eggs (Carputo 2003). The most important post-zygotic barrier in potatoes is EBN.…”
Section: Discussionmentioning
confidence: 99%
“…e S. commersonii subsp. malmeanum Bitt., que possuem alelos de resistência a baixas temperaturas, resistência à murcha bacteriana causada por Ralstonia solanacearum e à podridão mole e canela preta causadas por Erwinia carotovora, além de apresentar um alto teor de matéria seca (CARPUTO, 2003;ROCHA et al, 2000).…”
Section: (Recebido Em 4 De Novembro De 2005 E Aprovado Em 10 De Abrilunclassified
“…The strategy was based on doubling the chromosome number of CMM, and on the production of 3x(2EBN) bridges derived from 4x × 2x crosses between 4x(2EBN) CMM and 2x(2EBN) genotypes. Since the triploids produced 2n eggs, they could be used in 3x × 4x crosses with TBR to obtain (near)pentaploid bridges displaying a high level of aneuploidy (Carputo 2003). The unique ploidy of the genotypes produced made this material suitable for broadening our understanding of the cytological, genetic and reproductive behavior of genotypes with odd ploidies.…”
Section: Introductionmentioning
confidence: 99%